Can Countries Manage Their Financial Conditions Amid Globalization? - Arregui, Nicolas (IMF Working Papers; Working Paper ;, 2018)
This paper examines the evolving importance of common global components underlying domestic financial conditions. It develops financial conditions indices (FCIs) that make it possible to compare a large set of advanced and emerging market economies. It finds that a common component, 'global financial conditions,' accounts for about 20 percent to 40 percent of the variation in countries' domestic FCIs, with notable heterogeneity across countries. Its importance, however, does not seem to have increased markedly over the past two decades. Global financial conditions loom large, but evidence suggests that, on average, countries still appear to hold considerable sway over their own financial conditions-specifically, through monetary policy. Nevertheless, the rapid speed at which foreign shocks affect domestic financial conditions may also make it difficult to react in a timely and effective manner, if deemed necessary.